Discursive dynamics and local contexts on Twitter: The refugee crisis in Europe - Warin, Thierry; Stojkov, Aleksandar (Discourse & communication, 2023)
In today’s hybrid media environment, traditional news organizations extend their presence on Online Social Networks (OSNs) and compete with political and civil society organizations, public figures, and other influential digital storytelling individuals. This article examines conversations on Twitter, one of the most widely used OSNs, about Europe’s refugee crisis in 2014 and 2015. We use, in particular, topic modeling techniques to deduce the existence of a complex network of Twitter topics formed in response to coverage of and opinion formation surrounding the European refugee crisis. We collected more than 11 million tweets in six different languages. One of our most significant findings is that while most conversations happen in English, the refugee crisis has had different rhythms in other languages. Our assumption is that this could be evidence that the power of mainstream local media on Twitter to set the agenda is considerable, at least regarding refugee-related conversations in Europe.